Examining criteria for adulthood among young people in Sabah (East Malaysia) - Walton Wider; Norazah Mohd Suki; Melanie L. Lott; Larry J. Nelson; Sew, Kim Low; Getrude Cosmas (Springerlink, 2021)
This study aims to identify perceived adult status and to explore the criteria for adulthood of young people in Sabah (East Malaysia). The differences in such criteria based on gender and student status are also examined. Data collected from 208 respondents were analyzed via confirmatory factor analysis (CFA) and one-way analysis of variance (ANOVA). The empirical results of CFA revealed six criteria for adulthood: family capacities, norm compliance, interdependence, biological transitions, role transitions, and chronological transitions. However, the independence factor was discarded for further analysis because of having weak item loadings. In addition, the ANOVA test showed that women have higher interdependency and higher family capacities than men. Traditionally, women are more “other-oriented”—frequently thinking about the perspectives and needs of others—and are acknowledged as the main caregivers for children. Students are found to emphasize role transitions and biological transitions in determining their adulthood more than nonstudents. The present findings enable policymakers to obtain current emerging adults’ views regarding the differences in criteria for adulthood based on gender and student status. Present findings permit a better understanding of the value of emerging adults’ mental health as they encounter social, emotional, psychological, and physical challenges. This awareness would facilitate the provision of appropriate developmental programs for emerging adults to assist them in achieving adulthood. Directions for future research are also provided.